Optical Metamaterials Fundamentals and Applications - Cai, Wenshan. (Springer New York, 2010)
Metamaterialsartificially structured materials with engineered electromagnetic propertieshave enabled unprecedented flexibility in manipulating electromagnetic waves and producing new functionalities. In just a few years, the field of optical metamaterials has emerged as one of the most exciting topics in the science of light, with stunning and unexpected outcomes that have fascinated scientists and the general public alike. This volume details recent advances in the study of optical metamaterials, ranging from fundamental aspects to up-to-date implementations, in one unified treatment. Important recent developments and applications such as superlenses and cloaking devices are also treated in detail and made understandable. Optical Metamaterials will serve as a very timely book for both newcomers and advanced researchers in this rapidly evolving field. Early praise for Optical Metamaterials: "...this book is timely bringing to students and other new entrants to the field the most up to date concepts. The authors are amongst the leaders in the field and ideally positioned to write such a comprehensive volume: their enthusiasm shines through every chapter of the text. This book will I am sure play an important part in taking the subject of metamaterials to new heights of invention and application. We should all have a copy on our shelves." Professor Sir John Pendry, Imperial College London "This book provides an understandable introduction to the field of optical metamaterials, including all the necessary background and a comprehensive review of this new paradigm in the science of light. Professor Shalaev, a world-leading expert in optics and metamaterials, and his former student, Dr. Cai, a rising star in his own right, have skillfully developed a volume that will prove important for both experts and students just entering the exciting field of photonic metamaterials and transformation optics. This book will certainly find a place within easy reach on my shelf." Professor Victor G. Veselago, A.M.Prokhorov Institute of General Physics, Moscow "This is a nice treatment and a lucid description of the rapidly growing field of optical metamaterials. In this book, Wenshan Cai and Vladimir Shalaev have done a tremendous job in making this exciting scientific topic accessible to those interested in this field. They have discussed its fundamental concepts and potential applications in a clear and engaging way, providing the reader with a fascinating overview of this active area of research. I enjoyed reading this book, and I highly recommend it to all who wish to learn about the optical metamaterials. It tells a fascinating story about this field of optical science and engineering." Nader Engheta, H. Nedwill Ramsey Professor of Electrical and Systems Engineering, University of Pennsylvania